Agenesis of the gallbladder and choledocholithiasis: Case report. - Daniel Rodrigo Riaño Pinto (Case Reports)
The most frequent elective procedure in general surgery in adults is cholecystectomy. During the procedure, many abnormalities may be found in the gallbladder and the common bile duct, being agenesis of the gallbladder the most uncommon, which can be difficult to manage even for an experimented surgeon. This type of malformation has the lowest incidence in the bile ducts, with only about 400 cases reported in the literature (1).